Sosialisasi New Normal Masa Covid- 19 di Paroki Terentang Keuskupan Sanggau - Magdalena, Magdalena; Atok, Kristianus; Andreas Acin, Mayong; Lisarani, Varetha; Zulkairnain, Rezkie (Amare, 2022)
This activity is motivated by the Church's need to prepare its people so that they can adjust to new normal conditions as a result of the pandemic. After more than four months the churches were closed, sacramental services were restricted, even impossible to do – certainly not out of fear, but for the sake of common salvation. On that basis, community service activities, especially the parishioners of Terentang, are carried out so that they have the ability to make hand sanitizer. This activity was carried out for one day with the method of conducting exposure and followed by training activities. This activity was attended by 36 participants. The output of this activity is that all participants have the knowledge and skills to make hand sanitizers to support activities at the Terentang Parish Church.